Characteristics of patients hospitalized at an intensive care unit due to drug abuse - Flávia Antunes; Magda Lúcia Félix de Oliveira (Universidad de Antioquia, 2013)
Objective. To characterize the clinical and demographic profile of patients hospitalized due to drug intoxication at an intensive care unit (ICU) of a teaching hospital between 2004 and 2010. Methodology. In this descriptive study, information was collected from the hospitalized patients, as informed by a Toxicology Care Center (CAT) in Paraná (Brazil). The clinical files were checked and information was collected about age, gender, toxic agents and intoxication circumstances, comorbidities and clinical outcomes. Results. Sixty-two patients were included in the study, with a mean age of 58 years and 77% male. Alcohol was the substance related to most hospitalizations (77%), followed by psychoactive drugs (14%) and marihuana and crack (5% each). The main comorbidities were bronchopneumonia due to aspiration (37%), alcohol-related liver cirrhosis (24%) and traumatic brain injury (19%). The most frequent intoxication circumstances were chronic abuse (79%), attemptive suicide (19%) and acute abuse (4.9%). Thirty-nine percent of the patients died during hospitalization. Conclusion. The results show a concerning reality, as most of the patients are men of economically active age, who were intoxicated by a legal substance like alcohol, with a relevant number of deaths. Nurses need to pay particular attention to this health problem, in the context of which they play a fundamental role as educators with a view to the encouragement of healthy lifestyles.